Investigation of the predictive validity of laser‐EPs in normal, UVB‐inflamed and capsaicin‐irritated skin with four analgesic compounds in healthy volunteers. (27th February 2017) - Schaffler, Klaus; Nicolas, Laurent B.; Borta, Andreas; Brand, Tobias; Reitmeir, Peter; Roebling, Robert; Scholpp, Joachim
Abstract : Aims: The aim of the present study was to assess the predictivity of laser‐(radiant‐heat)‐evoked potentials (LEPs) from the vertex electroencephalogram, using an algesimetric procedure, testing the anti‐nociceptive/anti‐hyperalgesic effects of single oral doses of four marketed analgesics (of different compound classes) vs. placebo, in healthy volunteers with three skin types. Methods: This was a randomized, placebo‐controlled, single‐blind, five‐way‐crossover trial. Twenty‐five healthy male/female Caucasians were included (receiving celecoxib 200 mg, pregabalin 150 mg, duloxetine 60 mg, lacosamide 100 mg or placebo) in a Williams design, with CO2 laser‐induced painful stimuli to normal, ultraviolet (UV) B‐inflamed and capsaicin‐irritated skin. LEPs and visual analogue scale ratings were taken at baseline and hourly for 6 h postdose from all three skin types. Results: In normal skin, the averaged postdose LEP peak‐to‐peak‐(PtP)‐amplitudes were reduced by pregabalin (−2.68 μV; 95% confidence interval (CI) −4.16, 1.19) and duloxetine (−1.73 μV; 95% CI −3.21, −0.26) but not by lacosamide and celecoxib vs. placebo. On UVB‐irradiated skin, reflecting inflammatory pain, celecoxib induced a pronounced reduction in LEP PtP amplitudes vs. placebo (−6.2 μV; 95% CI −7.88, −4.51), with a smaller reduction by duloxetine (−4.54 μV; 95% CI −6.21, −2.87) and pregabalin (−3.72 μV; 95% CI −5.40, −2.04), whereas lacosamide was inactive. LEP PtP amplitudes on capsaicin‐irritated skin, reflecting peripheral/spinal sensitization, as in neuropathic pain, were reduced by pregabalin (−3.78 μV; 95% CI −5.31, −2.25) and duloxetine (−2.32 μV; 95% CI −3.82, −0.82) but not by celecoxib or lacosamide vs. placebo, which was in agreement with known clinical profiles. Overall, PtP amplitude reductions were in agreement with subjective ratings. Conclusions: LEP algesimetry is sensitive to analgesics with different modes of action and may enable the effects of novel analgesics to be assessed during early clinical development.